2(x-1)=4-(x-7)

Simple and best practice solution for 2(x-1)=4-(x-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x-1)=4-(x-7) equation:


Simplifying
2(x + -1) = 4 + -1(x + -7)

Reorder the terms:
2(-1 + x) = 4 + -1(x + -7)
(-1 * 2 + x * 2) = 4 + -1(x + -7)
(-2 + 2x) = 4 + -1(x + -7)

Reorder the terms:
-2 + 2x = 4 + -1(-7 + x)
-2 + 2x = 4 + (-7 * -1 + x * -1)
-2 + 2x = 4 + (7 + -1x)

Combine like terms: 4 + 7 = 11
-2 + 2x = 11 + -1x

Solving
-2 + 2x = 11 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
-2 + 2x + x = 11 + -1x + x

Combine like terms: 2x + x = 3x
-2 + 3x = 11 + -1x + x

Combine like terms: -1x + x = 0
-2 + 3x = 11 + 0
-2 + 3x = 11

Add '2' to each side of the equation.
-2 + 2 + 3x = 11 + 2

Combine like terms: -2 + 2 = 0
0 + 3x = 11 + 2
3x = 11 + 2

Combine like terms: 11 + 2 = 13
3x = 13

Divide each side by '3'.
x = 4.333333333

Simplifying
x = 4.333333333

See similar equations:

| =10a+15b | | 9h^2-1/9h^2+6h+1 | | (y^2+6x^2y)dx+(2xy+2x^3)dy=0 | | 1/5x+x=90 | | x-3=5*x+25 | | 9x-(4x+10)=30 | | a-(3a+b)= | | (6x+10)3/7 | | x=35-782 | | 5(2y+4)+2(5-y)=6 | | 5X-17=-2X-4 | | 7-3(10-2y)=-5 | | 5X-17=2X-4 | | 3(2x-4)-(5x+2)=11 | | 3(4x+4)-2(3-x)=48 | | 13x+30=6x+114 | | 4x-2(3x+10)=8 | | 10-2x-5=-4x+10-3x | | 5-3x+5=5+2x | | 29-60/7 | | 6x+7=133-8x | | 6-5x-2x=3-5x | | X^2-9x-81= | | 3+2x-4x=4-x+4 | | 3(x-6)=72/12 | | 5x+0.8=x | | 7/x=5/4x+1 | | r^2-30r+29= | | 17-3a=5a+1 | | 3u-25u/6+20=18 | | 360=2x(x+3) | | 4(5+3)=3c-5 |

Equations solver categories